2022
DOI: 10.1111/pim.12911
|View full text |Cite
|
Sign up to set email alerts
|

Hookworm infections: Reappraising the evidence for a role of neutrophils in light of NETosis

Abstract: In Hookworm infection, neutrophils have long had the image of the villain, being recruited to the site of larval migration because of damage but participating themselves in tissue injury. With recent developments in neutrophil biology, there is an increasing body of evidence for the role of neutrophils as effector cells in hookworm immunity. In particular, their ability to release extracellular traps, or neutrophil extracellular traps (NETs), confer neutrophils a larvicidal activity. Here, we review recent evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 93 publications
1
4
0
Order By: Relevance
“…Eosinophils as well as neutrophils formed extracellular traps (as reported for parasites in the pleural cavity; Ehrens et al, 2021a ), and each cell type contributed key toxic molecules (major basic protein and myeloperoxidase, respectively), in a manner enhanced by specific antibody ( Ehrens et al, 2021b ). The demonstration of trap formation at the physiological site of infection builds on earlier work showing NET formation against the human parasite Strongyloides stercoralis in vitro and following intraperitoneal injection into mice ( Bonne-Année et al, 2014 ), and fits within a recognition of the broader roles of neutrophils in immunity to helminths ( Chen et al, 2014 ; Doolan and Bouchery, 2022 ). This study epitomizes the key points of immunity to helminths, in which each species is targeted by a bespoke combination of innate effector cell populations that are dependent on adaptive immune activation and the specific tissue site of invasion, ultimately deploying multiple molecular strategies to eliminate the parasite ( Fig.…”
Section: Immunity In the Skin: Tricks And Trapssupporting
confidence: 56%
“…Eosinophils as well as neutrophils formed extracellular traps (as reported for parasites in the pleural cavity; Ehrens et al, 2021a ), and each cell type contributed key toxic molecules (major basic protein and myeloperoxidase, respectively), in a manner enhanced by specific antibody ( Ehrens et al, 2021b ). The demonstration of trap formation at the physiological site of infection builds on earlier work showing NET formation against the human parasite Strongyloides stercoralis in vitro and following intraperitoneal injection into mice ( Bonne-Année et al, 2014 ), and fits within a recognition of the broader roles of neutrophils in immunity to helminths ( Chen et al, 2014 ; Doolan and Bouchery, 2022 ). This study epitomizes the key points of immunity to helminths, in which each species is targeted by a bespoke combination of innate effector cell populations that are dependent on adaptive immune activation and the specific tissue site of invasion, ultimately deploying multiple molecular strategies to eliminate the parasite ( Fig.…”
Section: Immunity In the Skin: Tricks And Trapssupporting
confidence: 56%
“…Meanwhile, numerous reports have studied the crucial role of NETosis against inv sive protozoan [2,32,43,44,58,[63][64][65][66] and helminth parasites [2,6,40,67,68]. However, s far, there is only one report on C. parvum-induced suicidal NETosis in the literature [2 We have shown that C. parvum sporozoite and oocyst-mediated suicidal NETosis occu by establishing co-localization of nuclear H1A, H2A/B, H3-4, and NE in DNA-rich NE complexes produced by C. parvum.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, numerous reports have studied the crucial role of NETosis against invasive protozoan [2,32,43,44,58,[63][64][65][66] and helminth parasites [2,6,40,67,68]. However, so far, there is only one report on C. parvum-induced suicidal NETosis in the literature [2].…”
Section: Discussionmentioning
confidence: 99%
“…The DNA webs exhibited both trapping and direct killing properties against the infective (L3) larvae by inducing cuticle damage (Figure 2C), resulting in increased permeability to the DNA binding dye Sytox-Green. Temperature activation enhanced the larval secretion of the DNase-II enzyme, which was capable of degrading the NET strands to escape trapping and cuticle damage [65].…”
Section: Direct Killing (Larvicidal) Effectsmentioning
confidence: 99%